Application of the Independent Curriculum in Indonesian Language Learning at SMAN 4 Tapung - vina, Tasya Amelia Yoridan; Afandi, Vina Rahma; Yalawa, Yoridan; Mukhlis, Muhammad (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
This study aims to describe the results of the Implementation of the Independent Curriculum in Indonesian Language Learning at SMAN 4 Tapung. The subjects in this study were teachers at SMAN 4 Tapung. The data in this research are primary data and secondary data. There are three data sources in this study. First, Indonesian teacher, second Indonesian teacher, and third Indonesian teacher. The instrument of this research is joint research. The results of this study are twelve. First, the teacher has implemented the independent curriculum in Indonesian language learning. Second, the implementation of the independent curriculum brings positive changes to student behavior. Third, the learning materials for the independent curriculum are better than before. Fourth, the teacher makes students apply P5 (projects, strengthening, profiles, students, Pancasila). Fifth, the application of various learning facilities in schools. Sixth, the teacher gives freedom in using learning resources. Seventh, the teacher applies the type of assessment for the national exam, namely AKM. Eighth, implementing socialization in AKM and character surveys. Ninth, exercise freedom in designing learning activities according to the context and needs of students in the independent curriculum. Tenth, preparing lessons in Indonesian made by the teacher in the form of teaching modules. Eleventh, the application of methods and strategies in implementing the independent curriculum teaching modules in Indonesian. Twelfth, the teacher applies a student-centered learning model.